The emerging role of cancer nanotechnology in the panorama of sarcoma - Mercatali, Laura; Vanni, Silvia; Miserocchi, Giacomo; Liverani, Chiara; Spadazzi, Chiara; Cocchi, Claudia; Calabrese, Chiara; Gurrieri, Lorena; Fausti, Valentina; Riva, Nada; Genovese, Damiano; Lucarelli, Enrico; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
In the field of nanomedicine a multitude of nanovectors have been developed for cancer application. In this regard, a less exploited target is represented by connective tissue. Sarcoma lesions encompass a wide range of rare entities of mesenchymal origin affecting connective tissues. The extraordinary diversity and rarity of these mesenchymal tumors is reflected in their classification, grading and management which are still challenging. Although they include more than 70 histologic subtypes, the first line-treatment for advanced and metastatic sarcoma has remained unchanged in the last fifty years, excluding specific histotypes in which targeted therapy has emerged. The role of chemotherapy has not been completely elucidated and the outcomes are still very limited. At the beginning of the century, nano-sized particles clinically approved for other solid lesions were tested in these neoplasms but the results were anecdotal and the clinical benefit was not substantial. Recently, a new nanosystem formulation NBTXR3 for the treatment of sarcoma has landed in a phase 2-3 trial. The preliminary results are encouraging and could open new avenues for research in nanotechnology. This review provides an update on the recent advancements in the field of nanomedicine for sarcoma. In this regard, preclinical evidence especially focusing on the development of smart materials and drug delivery systems will be summarized. Moreover, the sarcoma patient management exploiting nanotechnology products will be summed up. Finally, an overlook on future perspectives will be provided.